2018
DOI: 10.1111/xen.12381
|View full text |Cite
|
Sign up to set email alerts
|

P‐ and E‐selectin receptor antagonism prevents human leukocyte adhesion to activated porcine endothelial monolayers and attenuates porcine endothelial damage

Abstract: Selectin blockade may be useful as part of an integrated strategy to prevent neutrophil-mediated organ xenograft injury, especially during the early time points following reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…In agreement with our work it has been demonstrated that inhibition of E-and P-selectin led to reduced rolling of neutrophils on endothelium reducing the risk of neutrophil-mediated endothelial injury after xenotransplantation (40). Further, in CML, we had previously shown that deficiency of E-selectin in bone marrow endothelium or deficiency of L-selectin, Pselectin glycoprotein ligand (PSGL)-1, enzymes involved in the synthesis of selectin ligands (6) or CD44 (8) on LIC were required for efficient engraftment of LIC, whereas P-selectin in the bone marrow was not required (6).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our work it has been demonstrated that inhibition of E-and P-selectin led to reduced rolling of neutrophils on endothelium reducing the risk of neutrophil-mediated endothelial injury after xenotransplantation (40). Further, in CML, we had previously shown that deficiency of E-selectin in bone marrow endothelium or deficiency of L-selectin, Pselectin glycoprotein ligand (PSGL)-1, enzymes involved in the synthesis of selectin ligands (6) or CD44 (8) on LIC were required for efficient engraftment of LIC, whereas P-selectin in the bone marrow was not required (6).…”
Section: Discussionsupporting
confidence: 93%
“…The first important step for the diapedesis is the interaction between the leukocytes and adhesion molecules on endothelial cells, including P-selectin (a cell adhesion molecule on the surfaces of activated endothelial cells); E-selectin (endothelialleukocyte adhesion molecule 1 expressed only on endothelial cells and activated by cytokines) (Laird et al, 2018); ICAM-1 (intercellular adhesion molecule-1 typically expressed on endothelial cells and cells of the immune system) (Schaefer et al, 2017); and VCAM-1 (vascular cell adhesion molecule-1 that mediates the adhesion of lymphocytes, monocytes, eosinophils, and basophils to vascular endothelium) (Fan et al, 2019). The next step involves the rolling of leukocytes along the wall of the vessel; the release of chemokines that strengthen contact with the endothelium; and the extension of pseudopods, from leukocytes, that allow the attack of endothelial cells (Lutz et al, 2017).…”
Section: From Metabolic Syndrome To Neurological Diseasesmentioning
confidence: 99%
“…Platelets and neutrophils in human blood bind porcine endothelial cells, leading to inflammation and ultimately organ failure. Laird et al used microfluidic channels coated with porcine endothelial cells and simulated physiologic flow conditions. The researchers tested novel antagonists for the cellular adhesion molecules E‐ and P‐selectin.…”
Section: Xenoprotectionmentioning
confidence: 99%